Pengembangan Sensor Kesegaran Buah Pepaya Potong (Carica Papaya L.) Pada Kemasan Pintar Berbasis Indikator pH Alami Kunyit (Curcuma Longa L.): Freshness sensor - Venny Diah Ningsih (Program Studi S1 Farmasi Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2021)
Papaya cut easily loses quality, so a smart label is needed to detect the freshness of the papaya cut.. Smart label for detecting papaya freshness are made by immobilizing whatmann filter paper membrane on the indicator of turmeric. Smart label have a 2 minutes response time, good reproducibility is indicated by the RSD values <5%, and the usage time is 15 days. Smart label have been successfully applied to detect freshness of cut papayas on the market